Cosmeceuticals - Comstock, Jody; Gold, Michael H. (Basel Karger, 2021)
Cosmeceuticals are ingredients or products that provide cosmetic and therapeutic benefits and which can be obtained without a prescription. They are one of the fastest growing segments in the personal care product market. Even in the worst economic climate, sales of cosmetics remain robust. Beauty enhancers are our best means of feel-good escapism, and we are not about to give them up. The ingredients, sales locations, and the regulation of sales are dynamic aspects of the industry. Here we give you a heads-up on where the market is going so you can make strategic decisions for your practice. This book will give you an understanding of facial cosmeceuticals examining the needs of the face, moisturizer formulation, noninvasive testing, and clinical evaluation to establish efficacy. It sheds light on topics such as the delivery mechanisms of active ingredients, vitamin A and C and other antioxidants, growth factors and stem cells, peptides, or amino acids. Topics also include the use of cosmeceuticals for the treatment of acne, rosacea, and hair loss and for hair care as well as the treatment of scars and cosmeceuticals for sun protection and protection from pollution. It also covers aspects of nutraceuticals and diets for healthy skin.
Keywords: COSMECÉUTICOS; COSMECÉUTICOS -- USO TERAPÉUTICO